2014
DOI: 10.1371/journal.pone.0108202
|View full text |Cite
|
Sign up to set email alerts
|

Human Fucci Pancreatic Beta Cell Lines: New Tools to Study Beta Cell Cycle and Terminal Differentiation

Abstract: Regulation of cell cycle in beta cells is poorly understood, especially in humans. We exploited here the recently described human pancreatic beta cell line EndoC-βH2 to set up experimental systems for cell cycle studies. We derived 2 populations from EndoC-βH2 cells that stably harbor the 2 genes encoding the Fucci fluorescent indicators of cell cycle, either from two vectors, or from a unique bicistronic vector. In proliferating non-synchronized cells, the 2 Fucci indicators revealed cells in the expected pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…Their results showed that the induction of advanced differentiation is correlated with the exit from the cell cycle of these cells (Carlier et al 2014). Our results showed that immature beta-cells actively transcribe proliferation-related genes and that a higher percentage of beta-cells from suckling and weaning rats could be found at S and G2/M phases of the cell cycle when compared with beta-cells from adult rats.…”
Section: Discussionsupporting
confidence: 48%
“…Their results showed that the induction of advanced differentiation is correlated with the exit from the cell cycle of these cells (Carlier et al 2014). Our results showed that immature beta-cells actively transcribe proliferation-related genes and that a higher percentage of beta-cells from suckling and weaning rats could be found at S and G2/M phases of the cell cycle when compared with beta-cells from adult rats.…”
Section: Discussionsupporting
confidence: 48%
“…Moreover, EndoC‐βH2 cells have recently been used to develop a third generation of human β‐cell line stably expressing a CRE‐ER chimera, hence undergoing oncogene excision upon tamoxifen treatment . EndoC‐βH2 cells were also used as a basis to develop additional tools, such as the human fucci pancreatic β‐cell line, which allows the study of human β‐cell cycle and terminal differentiation, and by using this we can try to understand why human β‐cells are so reluctant to proliferate …”
Section: Human β‐Cell Sourcesmentioning
confidence: 99%
“…If one estimates that 20–40% of β-cells were actively engaged in the cell cycle (Figs. 5 and 6); that half of these labeled cells represent new daughter cells and the other half represent the residual parent cells; that adenovirus transduction leads to cyclin/cdks expression after 24 h, leaving 4 days for β-cells to divide; and that, after replication, β-cells will divide only once during the 5 days of the experiment (25,4648), one can estimate that the yield of new daughter cells should be in the range of 30%. This is not dissimilar from the 29.6% increase in β-cell mass with the combination of early and late cyclins and cdks.…”
Section: Discussionmentioning
confidence: 99%